RISK MANAGEMENT IN VIA FERRATA CLIFF CLIMBING TOURISM ACTIVITIES IN MOUNT MENDELEM, PEMALANG REGENCY - Prameswari, Mentari Widya; Jacob Ganef Pah; Odang Permana (Politeknik Pariwisata NHI Bandung, 2023)
Today's tourism industry has experienced rapid changes due to the variety of tourists now wanting to obtain an authentic experience. In Indonesia itself, adventure tourism has become a prima donna since 2018 because it has brought 100,000 tourists from all over the world. This provides great economic value for the destination visited up to 67%. Via ferrata is one of the growing adventure tourism activities in Indonesia. Despite the high risk, this activity has a main market, which is the general public who want to experience rock climbing without having to have special abilities. In order to minimize these risks, it is necessary to have risk management so that the via ferrata can be made into extreme tourism but still safe for public tourists. The purpose of this research is to identify and find out the theoretical implications of risk management carried out via ferrata managers. Good risk management is applying industry management based on existing policies, standards, and procedures. The method used is qualitative descriptive with analysis using coding tools. Via ferrata does not yet have standard rules and SOPs. The new risk management is assessed based on the safety aspects of the safety equipment referring to the UIAA. All Mount Mendelem via ferrata operators do not have rock climbing certification and the existing SOP has not been written and the implementation is not suitable. Even so, in terms of security, the manager takes great care to create a tracking lane as an alternative to the down lane. So in this case the manager has applied the standards well but not yet for the policies and procedures used.